The Determinants of International Reserves in West-African States (Global Journal of Human-Social Science, 2018)
This study examined the relationship between international reserve and its determinants in west African States for the period of 2005 to 2014. The study was based on buffer stock model and was estimated using Panel ARDL approach. In the short run, All the variables except imports and NEER have a positive impact on international reserve. In the long-run, (IMP), export (EXA) and nominal effective exchange (NEER) does not have a statistical relationship with international reserves accumulation. I.